Biological roles of growth hormone/prolactin from an evolutionary perspective - Yasumasa Iwasaki; Mitsuru Nishiyama; Dylan Corcoran; Takako Araki (Endocrine Journal)
Although growth hormone (GH) and prolactin (PRL) are usually recognized as pituitary hormones, their expression is not restricted to the adenohypophysis and can also be found in extra-pituitary tissues including placenta. Furthermore, GH, PRL, and their receptors structurally belong to the cytokine family of proteins, and indeed they have remarkable pleiotropic effects. In this review, we analyzed the biological roles of GH/PRL from an evolutionary perspective. We have recognized that the biological significance of GH/PRL can be summarized as follows: cytokines (metabokines) that regulate the shift of nutrients and even of whole bodies to live in the most appropriate environment(s) for conducting growth and reproduction. In this sense, the common keyword of the two metabokines is “shift” for environmental adaptation. Considering that these metabokines flexibly changed their biological roles, GH/PRL may have played important roles during vertebrate evolution.